Theoretical foundations of investment banking - Krause, Andreas (Switzerland Springer, 2024)
Banking, and investment banking in particular, is to a large extent investigated empirically in the academic literature. The theory of investment banking behaviour and the relationship between investment banks and their clients is not widely known and applied to analyse developments in this industry. This book provides readers with a comprehensive and state-of-the-art overview of the theories of investment banking.